1985
DOI: 10.1071/ar9850063
|View full text |Cite
|
Sign up to set email alerts
|

Root characteristics of some temperate legume species and varieties on deep, free-draining entisols

Abstract: We report experiments comparing several legumes with the aim of distinguishing genotypic from environmental differences in those root parameters which influence water use and nutrition. Temperate crop and pasture legumes were grown on three xeric psamment soils at latitude 29�S. in Western Australia to evaluate the relative root characteristics of different species. Sites had 428, 298 and 155 mm rainfall in the (winter) growing season. Maximum root depth was significantly different (P < 0.001) between genot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
2
1

Year Published

1992
1992
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(44 citation statements)
references
References 0 publications
3
38
2
1
Order By: Relevance
“…The potential elongation rate for the lupin of 44 mm/day was taken as 10% higher than in the APSIM-Wheat model. This was supported by the findings by Hamblin and Hamblin (1985), Hamblin and Tennant (1987) and Anderson et al (1998b) who measured slightly deeper roots in lupin than in wheat in a range of soil types. However, and Gregory (1998) measured similar or lower values of root depth in lupin compared with wheat in a duplex soil.…”
Section: Crop Development and Growthsupporting
confidence: 76%
“…The potential elongation rate for the lupin of 44 mm/day was taken as 10% higher than in the APSIM-Wheat model. This was supported by the findings by Hamblin and Hamblin (1985), Hamblin and Tennant (1987) and Anderson et al (1998b) who measured slightly deeper roots in lupin than in wheat in a range of soil types. However, and Gregory (1998) measured similar or lower values of root depth in lupin compared with wheat in a duplex soil.…”
Section: Crop Development and Growthsupporting
confidence: 76%
“…There are few studies of roots of different species grown under comparable conditions and even fewer in which a species has been grown on the same site over several seasons. Hamblin and Hamblin (1985) compared the root growth of several species on deep Entisols at two locations in Western Australia and found that the ranking of total root length was pasture legumes (clovers and medics) > wheat > lupins and peas. Other comparisons of crop species also confirm the impression that temperate cereals have greater root lengths than temperate legumes when grown on the same site.…”
Section: Root Dry Mass and Partitioning In Major Arable Cropsmentioning
confidence: 99%
“…5A). Cereals such as wheat could extend their roots to an average 113 cm and had less than 50% of their total root length in the top 20 cm, while legume (i.e., field pea) to only 65 cm with more than 70% of the root system in the top 20 cm (Hamblin and Hamblin, 1985). This rapid development of deep rooting system in cereals enabled them to absorb water from deep soil horizon and contributed to the drought avoidance strategy within the crop group (Yue et al, 2006).…”
Section: Soil Texturementioning
confidence: 99%